Relation of thromboelastography parameters to conventional coagulation tests used to evaluate the hypercoagulable state of aged fracture patients. Issue 24 (June 2016) - Liu, Chen; Guan, Zhao; Xu, Qinzhu; Zhao, Lei; Song, Ying; Wang, Hui
Abstract : Abstract: Fractures are common among aged people, and rapid assessment of the coagulation status is important. The thromboelastography (TEG) test can give a series of coagulation parameters and has been widely used in clinics. In this research, we looked at fracture patients over 60 and compared their TEG results with those of healthy controls. Since there is a paucity of studies comparing TEG assessments with conventional coagulation tests, we aim to clarify the relationship between TEG values and the values given by conventional coagulation tests. Forty fracture patients (27 femur and 13 humerus) over 60 years old were included in the study. The change in their coagulation status was evaluated by TEG before surgery within 4 hours after the fracture. Changes in TEG parameters were analyzed compared with controls. Conventional coagulation test results for the patients, including activated partial thromboplastin time (APTT), international normalized ratio (INR), fibrinogen, and platelets, were also acquired, and correlation analysis was done with TEG parameters, measuring similar aspects of the coagulation cascade. In addition, the sensitivity and specificity of TEG parameters for detecting raised fibrinogen levels were also analyzed. The K (time to 20 mm clot amplitude) and R (reaction time) values of aged fracture patients were lower than controls. The values for angle, maximal amplitude (MA), and coagulation index (CI) were raised compared with controls, indicating a hypercoagulable state. Correlation analysis showed that there were significant positive correlations between fibrinogen and MA/angle, between platelets and MA, and between APTT and R as well. There was significant negative correlation between fibrinogen and K. In addition, K values have better sensitivity and specificity for detecting elevated fibrinogen concentration than angle and MA values. Aged fracture patients tend to be in a hypercoagulable state, and this could be effectively reflected by a TEG test. There were correlations between TEG parameters and corresponding conventional tests. K values can better predict elevated fibrinogen levels in aged fracture patients.